Prevalence of Hydatidosis in Sheep, Goats, Cattle, and Camels Slaughtered in Selected Abattoirs in Sabratha City, Libya - Murshid, Mohammed; Tarak Zahmoul; Elmabrok Masaoud; Elmabruk Gamag; Ayiman Almabrouk (AlQalam Journal of Medical and Applied Sciences, 2026)
Cystic echinococcosis (CE) is a widespread zoonotic parasitic disease that negatively affects both human health and livestock productivity. It represents a major medical and economic concern in many developing countries, including Libya. Nevertheless, the economic impact of CE in most endemic regions remains poorly characterized. The present study was conducted to assess the prevalence of hydatid cyst infection in key livestock species slaughtered in Sabratha, Libya. A total of 8,907 animals, including sheep, goats, cattle, and camels, were examined through post-mortem inspection of visceral organs. Overall prevalence varied significantly among species (p < 0.05), with cattle showing the highest infection rate (5.806%), followed by goats (4.942%), camels (4.292%), and sheep (3.447%). Seasonal analysis revealed higher prevalence during winter and spring, suggesting environmental influences on parasite transmission. Age-related patterns indicated consistently higher infection rates in older animals, supporting the role of cumulative exposure. Organ distribution analysis showed the liver and lungs as the most frequently affected organs across species. Females exhibited higher prevalence than males, likely reflecting management practices and longevity within herds. No significant difference was detected between local and imported animals, indicating widespread environmental contamination. These findings confirm the endemic nature of cystic echinococcosis in the study area and highlight the importance of integrated control measures, including improved slaughterhouse hygiene, proper offal disposal, and regular deworming of dogs. The study provides essential baseline epidemiological data to support surveillance programs and targeted control strategies in western Libya.